2011
DOI: 10.1038/emboj.2011.306
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of translation initiation on Aichivirus RNA mediated by a novel type of picornavirus IRES

Abstract: Picornavirus mRNAs contain IRESs that sustain their translation during infection, when host protein synthesis is shut off. The major classes of picornavirus IRESs (Types 1 and 2) have distinct structures and sequences, but initiation on both is determined by their specific interaction with eIF4G. We report here that Aichivirus (AV), a member of the Kobuvirus genus of Picornaviridae, contains an IRES that differs structurally from Type 1 and Type 2 IRESs. Its function similarly involves interaction with eIF4G, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
98
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(103 citation statements)
references
References 48 publications
4
98
1
Order By: Relevance
“…The data derived from functional analysis were in full agreement with the conservation of structural motifs in highly variable viral genomes, as well as with data from covariation analysis and computational RNA modeling which were used to define stable stems all along the FMDV IRES (Fernandez et al, 2011a;Jung and Schlick, 2013). Interestingly, the GNRA motif and the C-rich loop are conserved in IRES elements classified as type I or II (Fernandez et al, 2011a;Yu et al, 2011b). The GNRA motif, which is essential for IRES activity in both FMDV and EMCV (Lopez de Quinto and Martinez-Salas, 1997; Robertson et al, 1999), adopts a tetraloop conformation (Fernandez-Miragall and Martinez-Salas, 2003;Phelan et al, 2004), and determines long-range interactions (Fernandez-Miragall et al, 2006;Ramos and Martinez-Salas, 1999).…”
Section: Picornavirus Ires Elements Diversitysupporting
confidence: 56%
See 1 more Smart Citation
“…The data derived from functional analysis were in full agreement with the conservation of structural motifs in highly variable viral genomes, as well as with data from covariation analysis and computational RNA modeling which were used to define stable stems all along the FMDV IRES (Fernandez et al, 2011a;Jung and Schlick, 2013). Interestingly, the GNRA motif and the C-rich loop are conserved in IRES elements classified as type I or II (Fernandez et al, 2011a;Yu et al, 2011b). The GNRA motif, which is essential for IRES activity in both FMDV and EMCV (Lopez de Quinto and Martinez-Salas, 1997; Robertson et al, 1999), adopts a tetraloop conformation (Fernandez-Miragall and Martinez-Salas, 2003;Phelan et al, 2004), and determines long-range interactions (Fernandez-Miragall et al, 2006;Ramos and Martinez-Salas, 1999).…”
Section: Picornavirus Ires Elements Diversitysupporting
confidence: 56%
“…These elements are cis-acting RNA regulatory sequences endowed with the capacity to govern cap-independent translation initiation in mRNAs that are translated when cap-dependent translation is compromised. Subsequent studies demonstrated that IRES elements drive internal initiation of translation in the RNA of all members of the Picornaviridae family (Bakhshesh et al, 2008;Borman and Jackson, 1992;Brown et al, 1991;Hinton and Crabb, 2001;Hinton et al, 2000;Kaku et al, 2002;Kuhn et al, 1990;Nateri et al, 2000;Sweeney et al, 2012;Willcocks et al, 2011;Yu et al, 2011b). The genome of other RNA viruses also contains IRES elements, as illustrated by hepacivirus, pestivirus, dicistrovirus, retrovirus Tsukiyama-Kohara et al, 1992;Vallejos et al, 2010;Wilson et al, 2000), as well as some RNA viruses infecting plants and protozoa (reviewed in Martinez-Salas et al, 2012).…”
Section: Features Of the Picornavirus Untranslated Regionmentioning
confidence: 99%
“…The interaction sites of each RBD (RNA-binding domain) of PTB-1 are shown on the three IRES secondary structure maps, using the same color coding as in Figure 2B, namely: RBD-1 in green, RBD-2 in pink, RBD-3 in blue and RBD-4 in yellow (Kafasla et al 2009(Kafasla et al , 2010. The Aichivirus results showed that RBD-1 interacts strongly with the apical regions of both domains I and J, suggesting that these regions are closer to each other than can be shown on a two-dimensional diagram (Yu et al 2011), which explains the elongated depiction of RBD-1. No contacts between RBD-4 and the Aichivirus IRES were detected.…”
Section: Structure and Function Of Picornavirus Iress (And Some Compamentioning
confidence: 99%
“…Apart from one outlier, hepatitis Avirus (HAV), every picornavirus IRES can be placed unambiguously into one of four distinct groups: the long-standing Type I IRESs, which include HRV, PV, and other enteroviruses, and Type II IRESs, which include foot-and-mouth disease virus (FMDV) and EMCV (Alexander et al 1994;Jackson and Kaminski 1995); the more recently discovered Aichivirus (AV) group (Yu et al 2011); and the HCV-like group already mentioned. Within each of the two major picornavirus IRES classes (Types I and II), there is quite strong conservation of primary sequence, particularly in unpaired loops or bulges, and even stronger conservation of predicted secondary structure (Jackson and Kaminski 1995).…”
Section: Structure and Function Of Picornavirus Iress (And Some Compamentioning
confidence: 99%
See 1 more Smart Citation